Evaluation of Apical Microleakage in Endodontically Treated Teeth Using Three Sealer Materials: An In Vitro Study - Biland M.S Shukri; Haider Hasan Jasim; Mohammed Kassim Gholam (Wolters Kluwer Medknow Publications, 2022)
Introduction: GuttaFlow Bioseal (Roeko-Coltene/Whaledent, Langenau, Germany), TotalFill Bioceramic (FKG Dentaire SA, La Chaux-de-Fonds, Switzerland), and AH Plus root canal sealers (Dentsply, DeTrey, Germany) are used to prevent communication between periapical space and the root canal. This study aims to evaluate the apical microleakage of three endodontic sealers. Materials and Methods: Seventy-five freshly extracted mandibular premolars were prepared and obturated with single-cone gutta-percha, then grouped into three groups according to the sealers used. The data were analyzed using one-way analysis of variance (ANOVA) and Tukey honestly significant difference (HSD) test. Results: The least mean dye penetration was shown by GuttaFlow Bioseal sealer (1.31 mm), followed by TotalFill Bioceramic sealer (1.57 mm) and AH Plus sealer (2.63 mm); no dye penetration was found in the negative control group. One-way analysis of variance (ANOVA) showed statistically significant difference among all experimental groups (P < 0.001); Tukey test shows significant differences between all groups except for a nonsignificant difference between GuttaFlow Bioseal and TotalFill Bioceramic sealer (P = 0.6). Conclusion: All sealers showed varying levels of apical microleakage, with the least penetration in the GuttaFlow Bioseal group.